Prevalence of respiratory symptoms in school children and salivary IgA – an epidemiological study in a rural area of Northrhine-Westphalia, Germany - Hoelzer, Juergen; Stiller-Winkler, Renate; Lemm, Friederike; Witzke, Nicole; Ewers, Ulrich; Idel, Helga; Wilhelm, Michael (International journal of hygiene and environmental health, 2002)
An elevated frequency of wheezing was found in school children in a rural area of Northrhine-Westphalia, Germany (Duhme and Keil, Institut für Epidemiologie und Sozialmedizin, Universität Münster, Münster, Germany 1997). In this study the prevalence of wheezing was reinvestigated by including main influencing factors.A cross-sectional survey was performed in all school children visiting school classes 1, 2 and 7, 8 (n = 1161). Two corresponding questionnaires were used: a parental questionnaire and a questionnaire for self-completion by the children aged 12 – 15. The latter included the ISAAC video questionnaire. The levels of immunoglobulins A, G and M were determined in 995 saliva samples. Testing of lung function (whole body plethysmography before and after physical exercise) was performed in children with and without parent-reported wheezing in the last 12 months (n = 377).Response rate (questionnaire: 93%) and participation rates (saliva samples: 86 %, lung function tests: 93%) were high. Our study confirmed higher prevalence of asthmatic symptoms in children aged 6 – 8 in Ochtrup (13.2%) compared to children of the same age in Muenster (8.5% (Duhme et al., Eur. Respir. J. 11, 840 – 847, 1998)). However, in the age group 12 – 15 years the prevalence was significantly lower in Ochtrup (9.8%), when compared to the former investigation and in comparison to Muenster (former survey: 17.9%; Muenster: 13.1%). Prevalence of wheezing was consistently higher in families with atopic disease. Additionally, history of respiratory disease, premature birth and presence of pets during 1st year of life showed a positive association with prevalence of wheezing. Mean salivary IgA levels were 61.4 (SD (standard deviation) 35.1, median: 53.7) mg/l in children aged 6 – 8 years and 83.4 (SD 39.0, median: 76.3) mg/l in children aged 12 – 15 years. No significant association between salivary immunoglobulins and wheezing was detected.